Parent Perspectives on Participation in Family-Centered Rounds and Informational Resource Use - Glick, Alexander F.; Goonan, Michael; Sherman, Jacob; Sandmeyer, Diana; Gold-von Simson, Gabrielle (Frontiers in Pediatrics, 2020)
Objectives Family-centered rounds (FCR) can improve communication and patient/family engagement. While use of informational resources (e.g., tablets, computers on wheels, paper notes) can guide FCR, there are limited data concerning parental perspectives on how use of these resources during FCR, or other factors, affect their engagement. Our objectives were to examine parental perspectives on factors that affect their participation during FCR and preferences for informational resources used. Methods We performed a cross-sectional study with English-speaking parents (n=200), of pediatric inpatients at an academic medical center, present during FCR. We surveyed parents to ascertain factors they believed affect their engagement during FCR. We asked about their preferences regarding informational resources used by the medical team. Responses were analyzed using descriptive statistics. Parents described their reasoning behind resource preferences, and we categorized these responses. Results Parents reported that participation was affected by: clarity of the medical team’s explanations (78.5%), understanding the information (75.5%), the child’s health (74.5%), and being asked for their input (71%). Few (25%) parents believed the informational resource affects participation. Tablets were the preferred resource (24%) due to portability and ease of use, although 56% of parents had no preference. Conclusions Parents of hospitalized children placed importance on delivery of clear information and an “invitation” to participate during FCR. The resource used by the team was less important, although tablets were most preferred. Next steps are to examine factors associated with objective measures of participation and further study FCR in families with limited English proficiency.